2019
DOI: 10.1371/journal.pmed.1002936
|View full text |Cite
|
Sign up to set email alerts
|

Community-based football in men with prostate cancer: 1-year follow-up on a pragmatic, multicentre randomised controlled trial

Abstract: BackgroundPhysical exercise has been shown to be effective in relation to fatigue, aerobic fitness, and lower body strength in men with prostate cancer. However, research into the clinically relevant effects of interventions conducted in heterogeneous patient populations and in real-life clinical practice settings is warranted.Methods and findingsWe conducted a pragmatic, multicentre, parallel randomised controlled trial in 5 Danish urological departments. Recruitment began in May 2015, the first participant w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
73
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 36 publications
(74 citation statements)
references
References 29 publications
0
73
0
Order By: Relevance
“…Additionally, a recent injury cohort study reported that among 1,821 recreational soccer players (employees played each week-end), the incidence of injury was high leading to 1,196 days of labour loss, accounting for 211.5 days off per 1,000 match hours [74]. More recently, [75] showed no increase in severe injuries and the number of hospital admissions when playing soccer for one year on 200 elderly men with prostate cancer. Thus, it is recommended to avoid contact situations during SSSG.…”
Section: Practical Recommendations For Small-sided Soccer Games To Inmentioning
confidence: 99%
“…Additionally, a recent injury cohort study reported that among 1,821 recreational soccer players (employees played each week-end), the incidence of injury was high leading to 1,196 days of labour loss, accounting for 211.5 days off per 1,000 match hours [74]. More recently, [75] showed no increase in severe injuries and the number of hospital admissions when playing soccer for one year on 200 elderly men with prostate cancer. Thus, it is recommended to avoid contact situations during SSSG.…”
Section: Practical Recommendations For Small-sided Soccer Games To Inmentioning
confidence: 99%
“…Other studies were not specially designed for patients with bone metastases but included some, among others. Most of these studies defined painful or unstable bone metastases as exclusion criteria [ 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 ], medical clearance as a prerequisite [ 27 , 28 , 29 , 30 ] and/or modified the training program to enhance safety [ 29 , 30 , 31 ]. Only three studies reported no special attention when including patients with bone metastases [ 32 , 33 , 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, two studies had very small sample sizes (< 20), which increases the risk of biased results. In hindsight, several exercise-based RCTs have been conducted among patients with cancer, and even if older patients in general are underrepresented in exercise-based trials, some trials have a reasonable representation of older individuals [ 47 , 48 ] and/or may provide age-divided results.…”
Section: Discussionmentioning
confidence: 99%